Hyperbaric oxygen therapy as an adjunct for effective integration of dermal substitute with skin grafting in a single-staged procedure - Pradeoth Mukundan Korambayil; Prashanth Ambookan Varkey; Edwina Mary Babu; Vinoth Kumar Dilliraj (Journal of Clinical and Scientific Research)
Dermal substitutes are crucial in soft-tissue reconstruction, minimising donor-site morbidity. However, conventional protocols often involve multi-staged procedures. This case series explores the effectiveness of integrating dermal substitutes with skin grafting in a one-stage process for soft-tissue coverage, supplemented by hyperbaric oxygen (HBO) therapy. The study, conducted in the plastic surgery and burns department from June 2022 to December 2022, included 10 patients with soft-tissue defects. All underwent single-stage dermal substitute and skin grafting, accompanied by HBO therapy for soft-tissue reconstruction. Among the 10 patients, seven had soft-tissue defects in the leg region, comprising three with chronic ulcers, three with post-traumatic leg defects and one with a chronic ulcer due to peripheral vascular disease. Two patients had post-burn contracture release and reconstruction, while one presented with a soft-tissue defect following sternal wound dehiscence post-irradiation. All wounds healed successfully without complications, and all patients received six sessions of HBO therapy. The incorporation of HBO therapy as an adjunct proved beneficial in achieving successful single-stage reconstruction of soft-tissue defects using dermal substitutes and skin grafting.